2015
DOI: 10.15628/holos.2015.1455
|View full text |Cite
|
Sign up to set email alerts
|

Análises Estatísticas De Tendências Das Séries Hidro-Climáticas E De Ações Antrópicas Ao Longo Das Sub-Bacias Do Rio Tietê

Abstract: O objetivo deste estudo foi realizar análises estatísticas para identificar possíveis ocorrências de tendências em séries anuais de temperatura média do ar, precipitação pluviométrica e vazão de rios, registradas em cinco localidades que pertencem as sub-bacias hidrográficas do rio Tietê, no estado de São Paulo, Brasil. Foram empregados dados climáticos do Centro Integrado de Informações Agrometeorológicas (CIIAGRO) do Instituto Agronômico de Campinas (IAC), além dos dados hidrológicos do Sistema de Informaçõe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
2
Order By: Relevance
“…These low values are due to high uncertainties in studies on the rainfall regime. Ferreira et al (2015), Asfaw et al (2018) and Xu et al (2018) also found R 2 values always below 0.5 for the trend equations.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These low values are due to high uncertainties in studies on the rainfall regime. Ferreira et al (2015), Asfaw et al (2018) and Xu et al (2018) also found R 2 values always below 0.5 for the trend equations.…”
Section: Resultsmentioning
confidence: 87%
“…The behavior of the annual time series of meteorological variables was evaluated by adopting the calculation of the moving averages, employing the order five for the data, aiming to avoid fluctuations and smoothing the data (Ferreira et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, columns "P1" and "P2" show the intervention points determined by the Pettitt test (Salarizaji et al 2012;Ferreira et al 2015;Jaiswal et al 2015;Ahmad et al 2018;Penereiro and Meschiatti 2018;Gaponov et al 2019) for each period. In order to visualize the decreasing trends and the intervention points, we have elaborated the Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the use of linear regression, Mann-Kendall (Mann, 1945;Kendall, 1975) or both tests simultaneous has been used to identify a significant trend in climate data. In Brazil, these tests have been applied to identify significant changes in temperature (Ávila et al, 2014;Ferreira et al, 2015;Neves et al, 2016) and in rainfall (Ely and Dubreuil, 2017;Zilli et al, 2017). In the same way, worldwide studies were conducted to confirm changes in the weather variables mentioned previously (Chen and Zhai, 2017;Shi et al, 2018;Qian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%